Drug Abuse Among Elementary School Children: a Narrative Review of Implications For Islamic Ways of Prevention - Isa, Yakubu; Gidadawa, Fatima Abubakar (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
Elementary education is the key to further education. Drug abuse is a troubling issue in most societies, involving the misuse of drugs, such as using them without a prescription or just to cause intoxication. The aim of this study is to review the implications of drug abuse from the perspective of Islamic prevention methods. The study uses a qualitative method with a narrative review technique. The findings show that drug abuse has many negative impacts on both users and passive members of society. Muslim communities are also not spared from the grip of drug abuse, necessitating a religious-based intervention. Although education at the elementary level and beyond offers significant benefits, drug abuse poses an obstacle to achieving educational goals for children. Due to their vulnerabilities and lack of experience, children often fall into drug abuse. Drugs are substances that can alter bodily conditions. Children may be drawn into drug abuse due to various factors, such as peer pressure, lack of experience, genetics, environment, and others. Drug abuse can affect physical health, cause mental health problems, disrupt education, and create numerous social issues. Parents who adhere to Islamic laws in parenting can significantly reduce drug abuse among children. Following Islamic laws, such as the prohibition of drugs, will certainly address drug abuse among children in society.